2018
DOI: 10.1186/s12610-018-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Longer trinucleotide repeats of androgen receptor are associated with higher testosterone and low oxytocin levels in diabetic premature ejaculatory dysfunction patients

Abstract: BackgroundDespite its worldwide high occurrence, the obscurity regarding the description, epidemiology and management of premature ejaculation remains provocative. It is well established that male premature ejaculatory dysfunction is an increasing problem due to spontaneous ejaculation across a variety of general and clinical subjects. The main goal of this study was to determine the relationships between trinucleotide repeats of the androgen receptor (AR), sex steroids, and pituitary hormones with sexual func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…5-HT2C receptor agonists have been reported to improve glucose tolerance and insulin sensitivity in obese and diabetic mice [ 53 ]. It has been reported that DM patients with PE have lower levels of thyroid stimulating hormone (TSH) and PRL, which are also responsible for PE etiology, than healthy controls [ 54 ].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…5-HT2C receptor agonists have been reported to improve glucose tolerance and insulin sensitivity in obese and diabetic mice [ 53 ]. It has been reported that DM patients with PE have lower levels of thyroid stimulating hormone (TSH) and PRL, which are also responsible for PE etiology, than healthy controls [ 54 ].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…It has been shown that DM patients with PE have a strong association with a polymorphism constituting a long trinucleotide (CAG triplet) repeat sequence in the gene coding for the AR, compared to diabetics without PE 93 . The DM‐related PE in this study was diagnosed/measured using the IELT and score on the premature ejaculation diagnostic tool, both of which had significant correlation with the length of the CAG trinucleotide repeats in the AR gene 118 . The authors postulated this polymorphism may reflect hormonal modulation in the patient that mediates the PE; more specifically a raised T level and low oxytocin levels.…”
Section: Possible Predictors Of Ejd In Dmmentioning
confidence: 71%
“…93 The DM-related PE in this study was diagnosed/measured using the IELT and score on the premature ejaculation diagnostic tool, both of which had significant correlation with the length of the CAG trinucleotide repeats in the AR gene. 118 The authors postulated this polymorphism may reflect hormonal modulation in the patient that mediates the PE; more specifically a raised T level and low oxytocin levels. The former would seem to support studies proposing raised T levels increase the risk of PE.…”
Section: Genetic Pre-dispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that longer ( CAG )n repeats are considerably compromised the androgen receptor transcriptional activity, whereas short stretches are the cause of prostate cancer. However, the role of ( GGC )n repeats is still undefined (Khan et al ., a).…”
Section: Introductionmentioning
confidence: 99%